Object clustering method and device - CONSOLI SERGIO; VOS PIETER; HOFFMANN RALF; MAVRIEDUS, DANIEL; HENDRIKS MAIKEL; KUSTRA JACEK LUKASZ (2025)
A method of clustering or grouping objects similar to each other. The data set contains a set of quantitative values for each subject, each quantitative value representing a respective clinical or pathological characteristic of the subject. And performing principal component analysis (PCA) on the data set. The load of one of the first two principal components identified by the PCA is used to generate a corresponding data set of weighted values. These weighted values are used to weight or modify each set of quantitative values in the data set. A clustering algorithm is performed on the weighted object data set. The process may be iterated until a user-defined stop condition is satisfied. 一种对类似于彼此的对象进行聚类或分组的方法。数据集包含针对每个对象的定量值集合，每个定量值表示该对象的相应临床或病理特征。对所述数据集执行主成分分析PCA。通过所述PCA识别的头两个主成分中的一个主成分的载荷用来生成加权值的相应数据集。这些加权值用来对所述数据集中的每个定量值集合进行加权或修改。对加权对象数据集执行聚类算法。所述过程可以被迭代直到满足用户定义的停止条件。